TRANSPARANSI PELAYANAN PEMBUATAN E-KTP DI KECAMATAN JAILOLO KABUPATEN HALMAHERA BARAT - SELONG, MARGARETH; ROMPAS, WELSON; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract : E-ID card is a residence document containing security system / control both from administration side orinformation technology based on national demographic database. Making E-ID is wide open, easy, free and fast. In reality,obstacles in E-ID card service are still often found in E-ID card making service, among others most people have not get EIDcard dikarnakan, process that takes a long time, complicated, server system problem, poor infrastructure, lack ofattention and good response from employees, the number of queues in the process of making E-ID cards, and the certaintyof E-ID card issuance is not well implemented. Therefore, the researcher focused on Transparency of E-ID Card MakingService in Jailolo Sub-district, Halmahera Barat District. The purpose of this study is to analyze the Transparency of E-IDCard Making Service in Jailolo District. The research method used in this study is a qualitative approach where in researchconducted is descriptive that is to know or describe the reality of the events studied. The process of data analysis is done bystarting to examine all available data from various sources, namely obsevasi, interview, documentation and so on untilwithdrawal conclusion. Transparency of Public Service is openness and accountability of government related to service ofmaking E-ID to society. In this case the focus of research is the service procedure, technical and administrativerequirements, the service completion period, authorized and responsible officials, service promises, service standards, andlocation of services. The results of the research in the District of jailolo of West Halmahera showed that the Transparencyof E-ID Making Service conducted by the local government apparatus has not been fully transparent in providing servicesfor the community.Keywords: Transparency, Public Service.